Effect of foliar application of nitrogen and varieties on productivity and profitability of mungbean (Vigna radiata) in Afghanistan - SHAFIQULLAH BAHADARI; Y V SINGH; SHAH MAHMOOD BARAY; Y S SHIVAY; R PARSAD; SAYED AHMAD SAYEDI (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted in 2017 at ANASTU, Afghanistan to find the productivity and profitability of foliar application of nitrogen on different varieties of mungbean (Vigna radiata L. Wilczek) crop. The treatments included two mungbean varieties (Mash 2008 and NM 94) and seven methods of nitrogen applications including absolute control, basal application 25 kg N/ha, one time foliar application of 2% urea at 40, 50 and 60 days after sowing (DAS), two time foliar application at 50 and 60 DAS and three time foliar application of 2% urea spray at pre flowering (40 DAS), flowering (50 DAS) and pod development (60 DAS). The results showed that the variety Mash 2008 showed significantly higher seed and stover yields, harvest index, gross and net returns, production and monetary efficiency compared to NM 94.Among the nitrogen application treatments, 3 times foliar application of 2% urea at pre flowering + flowering + pod development stages (40, 50 and 60 DAS) was most suitable treatment to get highest growth, productivity, profitability and production and monetary efficiency of mungbean. It was concluded that the 3 times foliar of 2% urea at pre flowering + flowering + pod development stages (40, 50 and 60 DAS) may be applied to the variety Mash 2008 to get highest productivity and profitability of mungbean and this combination may be recommended under the semi-arid conditions of Afghanistan.